Avaliação de uma proteína hipotética específica de Leishmania no sorodiagnóstico e desenvolvimento de uma vacina contra as leishmanioses - Daniela Pagliara Lage (2016)
Leishmaniasis is a disease complex with a large incidence in Brazil and in the world, presenting high morbidity and mortality. Our country accounts for approximately 95% of the VL cases in Americas, being the dog the main domestic reservoir of the parasites. The serodiagnosis of canine visceral leishmaniasis (CVL) presents problems related to its sensitivity and/or specificity. In the present study, a Leishmania-specific hypothetical protein, rLiHyD, in a recombinant form (rLiHyD), was evaluated in ELISA experiments for the CVL serodiagnosis. Three B cell epitopes of LiHyD were synthesized (Peptide-1, Peptide-2 and Peptide-3) and also evaluated as diagnostic markers. The recombinant protein and the Peptide-3 showed the best results, being recognized by antibodies in sera from dogs with asymptomatic and symptomatic VL, and did not show cross-reactivity with antibodies in dog sera of dogs with Chagas disease, ehrlichiosis, babesiosis or animals without leishmaniasis and/or vaccinated with the Leish-Tec® vaccine. In the search to also select a candidate antigen for composing a vaccine against leishmaniasis, a combination between rLiHyD and saponin was tested in BALB/c mice against infection by Leishmania infantum, Leishmania major and Leishmania braziliensis. The immunogenicity of rLiHyD/saponin vaccine was evaluated, and the results showed that immunized mice produced higher levels of IFN-, IL-12 and GM-CSF after splenocytes in vitro stimulation with rLiHyD or L. infantum, L. major or L. braziliensis protein extracts. After challenge, vaccinated animals showed significant reductions in the parasite burden in all evaluated organs and tissues, when compared to those that were inoculated with saline or immunized with saponin or the protein alone. The protection obtained with the rLiHyD/saponin was associated with a parasite-specific IL-12dependent IFN- production, which was produced mainly by CD4+T cells. In these animals, a decrease in the parasite-mediated IL-4 and IL-10 responses, associated with the presence of high levels of LiHyD and parasite-specific IgG2a isotype antibodies, were also found. The present study showed that the hypothetical protein LiHyD, which was firstly identified in L. infantum, can be used for the CVL serodiagnosis and, when combined with a Th1 adjuvant, can compose a vaccine and confer protection against visceral and tegumentary leishmaniasis.